Secondary English Language Education Policy in Tourist Attraction School: Insight from Implementation - Santri, Dewi; Nurkhomsah, Umi (Proceeding International Conference on Religion, Science and Education, 2025)
The Merdeka Curriculum, a self-directed learning approach, is a key component of the English language teaching policy at SMP Negeri 1 Baturaden. The curriculum aims to create a communicative learning environment and develop proficiency in four language skills. Teachers play a crucial role in fostering creativity, innovation, and autonomy within this curriculum. The curriculum integrates relevant subjects, such as tourism, to provide students with practical life skills beyo nd the academic environment. The Merdeka Curriculum emphasizes the importance of matching strategies for teaching English with wider educational goals in a highly connected society. Despite challenges in integrating English into other disciplines, efforts are made to establish connections between content and improve the learning process. The Merdeka Curriculum incorporates well-defined objectives, varied teaching strategies, and suitable instructional resources. Practice-oriented language training, role-playing, and discussion exercises are used to enhance students’ motivation, creativity, and language skills. The study emphasizes the importance of understanding environmental resources and adopting an approach that focuses on utilizing the strengths within the school ecosystem to effectively manage resources and improve education quality. Overall, the Merdeka Curriculum is a comprehensive approach to teaching English language, focusing on modifying the curriculum, providing individualized training, and using policies to achieve larger educational goals.